Artikel: PERAN ORANG TUA DALAM MEMANFAATKAN MEDIA SOSIAL BAGI ANAK MASA SOCIAL DISTANCING - Silva Ardiyanti; Erni Munastiwi (Pendidikan Guru PAUD, FKIP, Universitas Muhammadiyah Tasikmalaya, 2020)
Social media is a tool that makes it easy for users to carry out various activities anytime, anywhere and with anyone without any time limit. Research This aims to describe the role of parents in utilizing social media for children during social distancing, a descriptive analytical qualitative approach is the approach and method used in this research Data collection uses observation, interview and documentation techniques, while the data collection tool is an interview guide. consists of 10 parents who have children aged 6-13 years and use social media Test the validity of the data through tringulation of data sources The results showed that the role of parents in utilizing social media for children during social distancing in terms of learning and developing creativity of young people well done, because parents have their own activities, especially the impact of Covid-19 makes their economic conditions difficult, while the cost of living increases, especially the purchase of internet quota in supporting the online learning process of children during social distancing.